Using Revit to Simulate and Improve Building Energy - Li, Yuanji; Zhao, Deyuan; Zhou, Guanqi (Transactions on Engineering and Technology Research, 2024)
Nowadays, the global attention to green buildings continues to increase, countries and regions have formulated the corresponding green building energy consumption standards and certification system, to evaluate and certify the energy-saving performance of buildings, in order to promote the development of green buildings. Green building projects continue to emerge everywhere, and green building technologies and materials are constantly innovating and developing. At present, many energy-saving technologies and strategies have been found: through the use of high-performance thermal insulation materials, thermal insulation materials, etc., to improve the thermal insulation performance of building structures, reduce the energy consumption of winter heating and summer cooling; Reasonable design of building heating, ventilation, air conditioning system, using efficient equipment and intelligent control system to improve energy efficiency; Make full use of natural lighting and natural ventilation, reduce the use time and intensity of artificial lighting and mechanical ventilation, and improve the natural lighting and ventilation effect of buildings. In the long run, energy-saving green buildings can reduce the operating costs of buildings through energy-saving measures, reduce greenhouse gas emissions and pollutant emissions generated in the process of energy consumption, and help reduce the energy consumption and environmental pollution of the construction industry, which is of great significance for mitigating climate change and improving environmental quality.